Nano-Management of Linear Properties of Photonic Crystal Fibers - Kacik, Daniel; Tatar, Peter; Liachovicky, David (Communications - Scientific letters of the University of Zilina, 2014)
The array of nanometer air holes positioned in the core can significantly modify the properties of guided mode in photonic crystal fiber. Changing geometrical properties of nanometer holes enables tuning of fiber dispersion and the effective mode area. This is related to losses of mode. In this paper, a rigorous analysis of dispersion and losses has been carried out for photonic crystal fiber with special arrangement of nanometer air holes in the core.